The Prevalence of Pinworm Infection in Children of District Mardan, Khyber Pakhtunkhwa, Pakistan - Ullah, Wasia; Nasir , Abdul; Izaz, Muhammad; Rabia (Indus Journal of Bioscience Research, 2025)
The aim of this study was to determine the Enterobius vermicularis prevalence in Khyber Pakhtunkhwa’s (KP) Mardan district. Five months, from December 2012 to April 2013, were used to gather the data. For the research, 140 kids between the ages of 1 and 14 were chosen at random. Enterobiasis was detected in stool samples by the direct smear technique. The findings of this study revealed that 27% (38/140) (p<0.05) of children had positive E. vermicularis tests. As compared to boys, girls had a greater prevalence. Age-wise study showed that children aged 1–5 years had the highest prevalence (34.33%) (p<0.05), while those aged 11–14 years had the lowest frequency (14.8%). Out of all the areas tested, Rashakai had the greatest incidence (34%). Monthly, the prevalence was at its lowest in April 2013 (17.4%) and at its highest in March 2013 (35.14%) (P < 0.05). The results indicate that E. vermicularis is highly prevalent in Rashakai, underscoring the necessity of focused treatments in this region. Therefore, a clean water supply, proper living conditions, cleanliness, and health education can all help to control and limit the infection. The study concludes that E. vermicularis prevalence varies by age, sex, region, and season. High rates in Rashakai and among children highlight the need for targeted interventions, including health education, improved sanitation, and routine screening, to effectively reduce infection burdens in vulnerable populations.